Improving Employee Performance Through Organizational Commitment As Mediating Variable - Wahyu Anggoro; Alex Zami; Humairoh Humairoh (Dinasti International Journal of Education Management And Social Science, 2024)
This research aims to analyze the influence of work discipline variables, quality of work life, work motivation and organizational commitment on the performance of employees of PT Wijaya Karya Gedung Gedung both simultaneously and partially. This research method is descriptive and verification with a quantitative approach. A sample of 235 people was determined using a saturated sampling technique. The analysis method uses Structural Equation Modeling (SEM) with Lisrel 8.80 Software. The three exogenous variables, both simultaneously and partially, were proven to be able to influence organizational commitment with a determination value (R2) = 73%. Partially, the work motivation variable is the variable that most dominantly influences organizational commitment with the most reflective dimensions and indicators, namely the dimension of labor requirements with indicators of labor equipment. Based on the results of the second substructure, the four exogenous variables have a positive and significant effect on employee performance with a determination value (R2) of 76%. Another important finding from this research is that organizational commitment acts as a complete mediating variable for the three variables in influencing employee performance.